The architect's apprentice [large type] - Shafak, Elif, 1971- (Center Point Large Print, 2015)
"During the height of the Ottoman Empire twelve-year-old Johan arrived in Istanbul to become an animal tamer to the white elephant Chota, befriend the sultan's beautiful daughter, and become an apprentice to Sinan, the empire's chief architect. As they build masterpieces, dangerous undercurrents begin to emerge, with jealousy erupting among Sinan's four apprentices"--